SAT0469 Osteoarthritis Is The Most Frequent Cause of Rheumathoid Arthritis Misdiagnosis in A Colombian Specialized Center. (15th July 2016) - Santos-Moreno, P.; Villarreal, L.; Ballesteros, G.; Bello, J.; Castillo, E.; Giraldo, R.; Gomez, D.; Aza, A.; Lopez, A.; Cardozo, A.; Palacio, N.; Buitrago-Garcia, D.; et al.
Abstract : Background: There is a lack of expertise in rheumatoid arthritis (RA) diagnosis in primary level of Colombian medical centers, leading to misdiagnosis; many times osteoarthritis (OA) and another rheumatic diseases are misdiagnosed as RA which derives in wrong treatment for patients with clinical and health economics implications. Objectives: The objective of this study was to describe demographic and clinical characteristics of a cohort of patients derived to a specialized RA center with presumptive RA diagnosis and finally diagnosed as osteoarthritis. Methods: A descriptive cross sectional study was done. Patients referred to a specialized RA center in a 48 month period with presumptive diagnosis of rheumatoid arthritis were assessed. Each patient was evaluated to confirm or rule-out diagnosis of RA as follows: a rheumatologist fulfilled a complete medical record, including all previous clinical, laboratories and imaging data; it was assessed rheumatoid factor, anti-citrullinated antibodies and other laboratories depending on each case. Also were made x-rays of hands and feet, and in some cases of persistent doubt about the diagnosis was requested comparative MRI of hands or/and feet. Frequencies and percentages were calculated for the demographic and clinical characteristics of the cohort of patients in which the diagnosis of RA was ruled-out. Results: A total of 5176 patients derived during the last four years to specialized in RA center with presumptive RA diagnosis, after medical, laboratory evaluation and imaging had a wrong RA diagnosis; of them patients 2930 (57%) had finally osteoarthritis diagnosis and of these patients 2594 (88%) were women and 336 (12%) men, with an average age of 59 ± 13 years old. Majority of these patients were followed by general physicians or internists and treated with non-biologic and some few cases with biologic disease modifying anti-rheumatic drugs (DMARDs) in the past years, for an average time of 4.5 years. Conclusions: In this cohort of patients the most frequent diagnosis of patients misdiagnosed with RA was osteoarthritis, being more than two thirds of them, predominantly women. This shows the need for the implementation of specialized clinics in RA and educational strategies for primary care physicians in order to avoid the impact of this wrong diagnosis. Disclosure of Interest: None declared